Effect of Cardiac Rehabilitation on Hope Among Cardiac Patients After Coronary Artery Bypass Graft Surgery - Rakhshan M; Toufigh A; Dehghani-firouzabadi A; Yektatalab S (Dove Medical Press, 2020)
Mahnaz Rakhshan,1 Afsoon Toufigh,2 Azimeh Dehghani-firouzabadi,3 Shahrzad Yektatalab1 1Nursing Department, School of Nursing and Midwifery, Shiraz University of Medical Sciences, Shiraz, Iran; 2Student Research Commitee, Shiraz University of Medical Sciences, Shiraz, Iran; 3Medical School, Shiraz University of Medical Sciences, Shiraz, IranCorrespondence: Mahnaz RakhshanNursing Department, School of Nursing and Midwifery, Shiraz University of Medical Sciences, Shiraz 71936-13119, IranTel +98 36474254Email rakhshanm@sums.ac.irPurpose: Following coronary artery bypass graft (CABG) surgery, some patients experience psycho-mental problems such as hopelessness. The Phase 2 cardiac rehabilitation (CR) program is an important element of the secondary prevention program in treating patients with cardiovascular disease (CVD). The present study aimed to determine the effect of the Phase 2 CR program on the level of hope in cardiac patients after CABG surgery.Patients and Methods: A clinical trial was conducted from July 2017 to late January 2018 at the Heart Surgery Centre, Al-Zahra Hospital, Shiraz, Iran. The target population was patients who sought CR therapy after CABG surgery. A total of 104 cardiac patients were recruited and equally divided into control and intervention groups. The intervention group received 20 sessions of Phase 2 CR program combined with education and counselling during 8 weeks. The control group only received routine observations and education. The data were collected pre- and post-intervention using a demographic form and the Miller Hope Scale (MHS). Descriptive statistics were expressed as percentages, frequency distribution, mean and standard deviation. Paired t-test and independent t-test were used for statistical inference. Data were analyzed using the SPSS statistical software (version 23.0) and P values < 0.05 were considered statistically significant.Results: There was no significant difference in the mean score of hope between the control and intervention groups before the intervention. However, a significant difference between the groups was observed post-intervention (P< 0.001). The results showed a significant difference in the mean score of hope between pre-intervention (182.36± 23.07) and post-intervention (216.94± 23.05) in the intervention group (P< 0.001), whereas the difference in the control group was not significant (P=0.095). The measured post-intervention effect size was high (1.05).Conclusion: The Phase 2 CR program combined with education and counseling increased hope in CVD patients after CABG surgery.Keywords: cardiac rehabilitation, CABG surgery, hope, nursing intervention